2016
DOI: 10.1021/acs.jpcc.5b10338
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Dissociation of CO2 on a Ni/CeO2(111)/Ru(0001) Model Catalyst

Abstract: The adsorption of CO2 on CeO2‑x (111) and Ni/CeO2‑x (111)/Ru­(0001) surfaces has been studied with reflection absorption infrared spectroscopy (RAIRS) and X-ray photoelectron spectroscopy (XPS). On the maximal-oxidized CeO2(111) surface physisorbed linear CO2 and a CO2 – species are identified at 97 K. The reduced CeO2‑x (111) surface exhibits higher reactivity toward adsorbed CO2, which leads to higher coverages of CO2 – and promotes CO2 dissociating into CO and an active oxygen species at higher temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 81 publications
4
21
0
Order By: Relevance
“…[12,13] To model nickel in close contact with stoichiometric and reduced ceria, we have considered aquarter of amonolayer of Ni atoms deposited on CeO 2 (111) and Ce 2 O 3 (0001) as ideal catalyst surfaces,aiming to elucidate the effects of the two supports in the Ni electronic and chemical properties towards CH 4 adsorption and dissociation as compared to Ni(111). [12,13] To model nickel in close contact with stoichiometric and reduced ceria, we have considered aquarter of amonolayer of Ni atoms deposited on CeO 2 (111) and Ce 2 O 3 (0001) as ideal catalyst surfaces,aiming to elucidate the effects of the two supports in the Ni electronic and chemical properties towards CH 4 adsorption and dissociation as compared to Ni(111).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 4 more Smart Citations
“…[12,13] To model nickel in close contact with stoichiometric and reduced ceria, we have considered aquarter of amonolayer of Ni atoms deposited on CeO 2 (111) and Ce 2 O 3 (0001) as ideal catalyst surfaces,aiming to elucidate the effects of the two supports in the Ni electronic and chemical properties towards CH 4 adsorption and dissociation as compared to Ni(111). [12,13] To model nickel in close contact with stoichiometric and reduced ceria, we have considered aquarter of amonolayer of Ni atoms deposited on CeO 2 (111) and Ce 2 O 3 (0001) as ideal catalyst surfaces,aiming to elucidate the effects of the two supports in the Ni electronic and chemical properties towards CH 4 adsorption and dissociation as compared to Ni(111).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…We found that Ni and Oatoms work in acooperative way to dissociate CH 4 molecules in accordance with previous theoretical works. [12,13] Once CH 3 is formed, sequential decomposition of this intermediate into Cshould occur very fast. [19] Adsorption sites with adjacent Ni and Oa toms exist in our catalysts since Ni forms solid solutions with ceria, Ce 1Àx Ni x O 2Ày .…”
Section: Angewandte Chemiementioning
confidence: 99%
See 3 more Smart Citations